2019
DOI: 10.1007/s11910-019-0918-y
|View full text |Cite
|
Sign up to set email alerts
|

CSF Biomarkers for Early Diagnosis of Synucleinopathies: Focus on Idiopathic RBD

Abstract: Purpose of Review Idiopathic REM sleep behavior disorder (iRBD) is one of the most significant prodromal manifestations of synucleinopathies. Different predictive biomarkers for iRBD conversion have been investigated, but scarce data are present in literature about the predictive role of cerebrospinal fluid (CSF) biomarkers. In this review, we focus on CSF biomarkers in patients with both iRBD and RBD associated with synucleinopathies to explore their potential predictive power. Recent Findings Recent studies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(1 citation statement)
references
References 52 publications
0
1
0
Order By: Relevance
“…There are diagnostic methods based on biomarker detection; cerebrospinal fluid (CSF) biomarkers Aβ 1-42 , T-tau, and P-tau are well-validated, and are being increasingly used in clinical practice as tools for the affirmative diagnosis of AD [ 41 ]. The long-term stability of core CSF biomarkers in patients with AD provides further support for their use in clinical studies and treatment monitoring in clinical trials [ 42 ]. Michael E. et al [ 43 ] proposed that CSF Aβ 1-42 showed the best diagnostic accuracy among the CSF biomarkers.…”
Section: Related Workmentioning
confidence: 99%
“…There are diagnostic methods based on biomarker detection; cerebrospinal fluid (CSF) biomarkers Aβ 1-42 , T-tau, and P-tau are well-validated, and are being increasingly used in clinical practice as tools for the affirmative diagnosis of AD [ 41 ]. The long-term stability of core CSF biomarkers in patients with AD provides further support for their use in clinical studies and treatment monitoring in clinical trials [ 42 ]. Michael E. et al [ 43 ] proposed that CSF Aβ 1-42 showed the best diagnostic accuracy among the CSF biomarkers.…”
Section: Related Workmentioning
confidence: 99%